Challenges in the management of familial hypercholesterolemia: a case report - Rogozik, Joanna; Grabowski, Marcin; Główczyńska, Renata (Frontiers in Cardiovascular Medicine, 2024)
Background Familial hypercholesterolemia (FH) is a serious genetic condition that results in abnormally high levels of low-density lipoprotein cholesterol (LDL-C) in the bloodstream, significantly increasing the risk of early onset of cardiovascular disease. The heterozygous form of FH (HeFH) is widespread, affecting around 1 in 500 people worldwide. Case report In this clinical report, we present the case of a patient who suffers from HeFH due to a mutation in the LDL receptor (LDLR) gene. A woman exhibited intolerance to statin therapy and did not attain adequate reduction in low-density lipoprotein cholesterol (LDL-C) levels on ezetimibe monotherapy. Genetic testing confirmed the presence of a pathogenic variant for FH with the deletion of exons 7–14. The administration of alirocumab (a dose of 150 mg sc) as the primary therapy did not exhibit the desired therapeutic outcome. Consequently, the patient was given inclisiran therapy (a dose of 284 mg sc), which significantly reduced LDL cholesterol levels after 3 months of treatment and during the 1-year follow-up. Conclusion Inclisiran therapy has shown promising results for individuals with HeFH who experience statin intolerance. This therapy works by using a small interfering RNA (siRNA) to target the mRNA of proprotein convertase subtilisin/kexin type 9 (PCSK9), which leads to a significant reduction of LDL-C levels. This approach can be an alternative for patients without significant reductions in LDL-C levels with PCSK9 inhibitor therapy. For HeFH patients with limited treatment options due to statin intolerance and genetic mutations, inclisiran can represent a promising therapeutic option.